Um círculo virtuoso: a relação entre lealdade e programas de fidelidade no varejo brasileiro - Jayme, Érica do Nascimento Ortiz (2021)
The objective of the study was to evaluate the role of loyalty in the participation and use of Loyalty Programs in the context of Brazilian retail, as well as motivators and effects generated by this resource on the participants' behavior. A systematic literature review was carried and allowed to establish the main factors that influence the adoption of LP by both managers and consumers. Loyalty publicized as a central factor in the LP debate. Phenomenological research was carried out by means of description with consumers participating in LP available on 49 transcribed pages. Data analysis shows that there is a cyclical relationship between loyalty and membership / participation in the LP. In other words, it is necessary that there is prior loyalty between the consumer and the brand so that the LP can exercise the function of reinforcing the existing loyalty. The results also showed that the personalization of offers and rewards in LP leads to repurchases and increases the cost of switching to the competition. The findings make it possible to recommend to marketing managers attention to the choice of the type of LP to be adopted with a focus on the most appropriate benefits to the target audience, the use of personalization of offers and extensive communication with participants to increase engagement with LP.